(untitled) (International journal of artificial intelligence, 2026)
The article examines the key advantages of interactive trainers in modern language education, including the individualization of learning, diversity of exercises, immediate feedback, gamified presentation of material, and accessibility for independent study. The study also considers the classification of educational trainers and their role in improving the effectiveness of foreign language acquisition. The findings demonstrate that the integration of interactive technologies significantly enhances learners’ motivation and learning outcomes.